Pengaruh Likuiditas, Leverage, dan Profitabilitas Terhadap Nilai Perusahaan Pada Perusahaan Farmasi - Komang Yulan Surmadewi, Ni; Dewa Gede Dharma Saputra, I (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.06.TAHUN 2019, 2019)
The purpose of this study is to analyze the effect of liquidity, leverage, and profitability on the value of the company on pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) for the period 2014-2017. The population of this research is pharmaceutical companies listed on the Indonesia Stock Exchange during the 2014-2017 period. Data collected by purposive sampling method, obtained as many as 9 companies that became research samples with a period of four years to obtain 36 research samples. The data analysis technique uses multiple linear regression analysis. Based on the results of the analysis it was found that the variable liquidity did not affect the value of the company. While the leverage and profitability variables significantly influence the value of the company. This shows the higher leverage and the higher the profitability, the higher the value of the company obtained.